The Double of the Word. The Myth of Echo in Contemporary English Literature - Monrós Gaspar, Laura (Amaltea. Revista de Mitocrítica, 2011)
This article explores the figure of Echo in contemporary English literature focusing on works by A.S. Byatt, Timberlake Wertenbaker, Nicole Ward Jouve and Moniza Alvi among others. After an introduction on the secondary literature published on the nymph, Echo is analyzed under the perspective of opposites such as self/other, metropolis/colony, word/silence in poetry, theatre and short stories. Considered en masse, the works discussed in this article manifest how the reception of Echo is closely linked to the concept of the double in Western cultures.